Memaknai Janji Pemulihan Yoel 2:18-27 di tengah Pandemi Covid-19 - Roy Charly Sipahutar (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2021)
This article is an attempt to find the deepest meaning of the text of Joel 2:18-27 for the life of Israel in the post-exilic period and which will be implemented in the present life. Unlike the prophetic texts in general which tend to contrast religious rituals with the crisis of social awareness of the nation of Israel, the text in this passage is actually a consolation and hope for a nation that has fallen as a result of commitment to undergo a new life order. Right life and right worship. The approach used to interpret the text is the Historical-Apocalyptic Hermeneutics to get God's message in the message of Joel. God apparently did not allow the survival of life on earth to be threatened, God listened to lamentations and noticed changes in the pattern of Israel's life so that it promised a peaceful future. The same promise would certainly be the consolation and hope of God's people today in the shock of Covid-19.